Effect of Life Skills Training on Dietary Behavior of School Adolescents in Delhi: A Nonrandomized Interventional Study. (March 2015) - Anand, Tanu; Ingle, G. K.; Meena, Gajendra Singh; Kishore, Jugal; Yadav, Sangita
Skill-based education has been shown to reduce high-risk behavior among adolescents, but in India, life skills have often been looked at only from the reproductive health perspective. Therefore, the current study was undertaken to assess the effect of life skills training on dietary behavior of adolescents studying in grades 9 and 11 of 2 schools in Delhi. This was a nonrandomized interventional study with a control group. A self-administered questionnaire was used for assessment of dietary behavior at baseline, 15 days, and 3 months after the life skills training. Two life skills training sessions were imparted to the intervention group, focusing on the use of life skills in making healthy choices. Participants in the intervention group (n = 180) showed significant improvement in knowledge ( P < .001), attitude ( P = .007), and practices ( P < .001) following the life skills training. To conclude, a skills-based approach does help improve the dietary behavior in adolescents.